1998
DOI: 10.1289/ehp.9810633
|View full text |Cite
|
Sign up to set email alerts
|

Human biomonitoring of arsenic and antimony in case of an elevated geogenic exposure.

Abstract: Part of the norther Palat e region in Germany is erized by elevated leels of arsenic and antimony in the soil due to the presence ofore sources and former mining activities. In a biomonitoring study, 218 residents were investigted for a putative increased intake of these elements. Seventy-six nonexposd subjects in a rur region in south lower Saxony were chosen as the rrece group. Urine and scalp hair sampes were obtained as su to dein he miteral exposures to arsenic and antimony. The analys were pefr*m ed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 52 publications
3
15
0
1
Order By: Relevance
“…Levels of urinary antimony in infants appeared to be similar to those reported by CDC (2005) for young children (Cullen et al, 1998;Dezateux et al, 1997). Urinary antimony was not associated with locally elevated soil levels in a study of more than 200 German residents (Gebel et al, 1998). Several investigations of airborne antimony exposures in workers have found urinary levels that are many times higher than those seen in NHANES 1999NHANES -2000NHANES , 2001NHANES -2002NHANES , and 2003NHANES -2004, even when exposure levels were below workplace air standards (Bailly et al, 1991;Iavicoli et al, 2002;Kentner et al, 1995;Liao Y-H et al, 2004;Ludersdorf et al, 1987).…”
Section: Biomonitoring Informationsupporting
confidence: 84%
“…Levels of urinary antimony in infants appeared to be similar to those reported by CDC (2005) for young children (Cullen et al, 1998;Dezateux et al, 1997). Urinary antimony was not associated with locally elevated soil levels in a study of more than 200 German residents (Gebel et al, 1998). Several investigations of airborne antimony exposures in workers have found urinary levels that are many times higher than those seen in NHANES 1999NHANES -2000NHANES , 2001NHANES -2002NHANES , and 2003NHANES -2004, even when exposure levels were below workplace air standards (Bailly et al, 1991;Iavicoli et al, 2002;Kentner et al, 1995;Liao Y-H et al, 2004;Ludersdorf et al, 1987).…”
Section: Biomonitoring Informationsupporting
confidence: 84%
“…Hinwood et al (2003) reported on higher As levels in toenails of male subjects, while in the report by Mandal et al (2003) As content in fingernails of females was higher than that of male subjects. Smoking was not a significant determinant of fingernail As levels, confirming observations from other European populations in which, however, As was measured in urine (Becker et al, 2003) or hair (Gebel et al, 1998). The lack of an influence of the As dietary intake on As in fingernails may be due to the fact that most As in the diet is organic As, which is probably not taken up into nails.…”
Section: As In Fingernails [µG/g] Urinary As (Assupporting
confidence: 80%
“…Smoking was not a significant determinant of urinary As levels, confirming studies in European populations (Gebel et al 1998;Kurttio et al 1998). Because of the high age of our study subjects, occupational exposure was of minor concern as confounder.…”
Section: Discussionsupporting
confidence: 81%